The prevalence and antimicrobial sensitivity of Esbl Escherichia Coli. in clinical isolates - Al-Attar, Zaid I. (AL-Kindy College Medical Journal, 2014)
Background: The antimicrobial resistance is one of the most serious and expanding health problems world -wide in the last decades. The esbl escherichia coli. (extended – spectrum beta-lactamase e.coli) represents an important aspect of it .Objectives: To get an overview on the esbl e.coli prevalence profile in general. Also to assess the antibiotic sensitivity of esbl e. coli trying to specify the most effective antibiotics in combating this micro-organism.Methods: this study tries to focus on this problem in Iraq which through a prospective study approach by taking 35 clinical samples from various sources (urine, blood, abscess, eye ,vagina ,stool and others),and after confirming the presence of e.coli, the presence of esbl e.coli and antibiotic sensitivity are confirmed by the use of Kirby - bauer method.Results: results showed that esbl e.coli constitutes 80% of the cases, while the results of antibiotic sensitivity were as follows: ampicillin 3.3% , ampicillin/sulbactam 20% , amoxi/clav 0%pipracillin/tazobactam 89.7% meropenem 96.7% ,imipenem 96.9% ,cefotaxime 0% ,ceftriaxone 11.8%,ceftazidime 16.1%,cefipime 14.3% ,cefazolin 16.1% cefoxitin 64.7%, aztreonam 14.3%,gentamycin 50% ,tobramycin 64.3%, amikacin 94.3%,ciprofloxacin 58.8% ,levofloxacin,64.5%nitrofurantoin,79.2%,trimethprimesulphamethoxazole 29.6% .Conclusion: the problem of esbl e.coli is expanding and there is a continuous demand for frequent monitoring of the new trends on antimicrobial resistance in different parts of the world in addition to trying to develop new antimicrobials to combat the new highly resistant strains .moreover there is a continuous need to educate the medical and the paramedical staff abot the risk of unjustified and improper prescription and use of antimicrobials.Key words: escherichia coli, extended-spectrum beta-lactamase, kirby-bauer method, muller hinton agar